Research Advances in Molecular Modeling in Cyclodextrins - Zhao, Qianqian; Zhang, Weixiang; Wang, Runmiao; Wang, Yitao; Ouyang, Defang (Current Pharmaceutical Design, 2017)
Background: Cyclodextrins (CDs), as one type of the novel pharmaceutical excipients, have been widely used in drug delivery and pharmaceutical industry. Over the past decades, a large amount of molecular modeling studies in CDs were reported for profound understanding of structural, dynamic and energetic features of CDs systems. Thus, this review is focused on qualitative and quantitative analysis of research outputs on molecular modeling in CDs. Methods: The original data were collected from Web of Science and analyzed by scientific knowledge mapping tools, including Citespace, Science of Science, VOSviewer, GPSvisualizer and Gephi software. Scientific knowledge mapping, as an emerging approach for literature analysis, was employed to identify the knowledge structure and capture the development of the science in a visual way. Results: The results of analysis included research outputs landscape, collaboration patterns, knowledge structure and research frontiers shift with time. China had the largest contributions to the publication number in this area, while USA dominated the high quality research outputs. International collaboration between USA and Europe was much stronger than that within Asia. J American Chemical Society, as one of the most important journals, played a pivotal role in linking different research fields. Furthermore, seven important thematic clusters were identified by the research cluster analysis with visualization tools and demonstrated from three different perspectives including: (1) the mostly-used CD molecules: β-Cyclodextrin, (2) preferred modeling tools: docking calculation and molecular dynamic, (3) hot research fields: structural properties, solubility, chiral recognition and solidstate inclusion complexes. Moreover, research frontier shift in the past three decades was traced by detecting keywords bursts with high citation. Conclusion: The current review provided us a macro-perspective and intellectual landscape to molecular modeling in CDs.
Keywords: Molecular dynamics